Physical Chemical Factors on Gastropod Distribution Patterns in Tritih Mangrove Forest Cilacap Central Java - wintah wintah; kiswanto kiswanto (Universitas Negeri Semarang, 2024)
The mangrove area in Tritih Cilacap, Central Java is decreasing due to illegal logging. This affects the distribution pattern of gastropods. This study aims to determine the distribution pattern of gastropods and provide information related to physical chemical factors that play a role in gastropod distribution patterns. This study was conducted at five sampling points. Five sampling points from the sea to the land. The sampling method used for gastropods was collection from 1x1 m plots. Gastropods in the plot were collected by hand on the top of the sediment and in the sediment were taken 10 cm deep using a corer with 3 repetitions for each station. Environmental parameters measured were: temperature, salinity, organic matter content, pH, and substrate type. The distribution of gastropods in Tritih Cilacap mangrove forest has a clustering and random pattern. There were 11 species of gastropods found from 7 families. Gastropod species that have clustered distribution patterns are: Ceritidhea alata, Telescopium telescopium, Neritina violacea, Neritina zigzag, Chicoreus capucinus, and Assimenia brevicula. Gastropod species that have random distribution patterns are: Ceritidhea quadrata, Neritina lineata, Cassidulla aurisfelis, Cassidulla nucleus, and Littoraria carinifera. The results of BIOENV analysis showed that the most influential environmental factors on gastropod density were water temperature, salinity, organic matter content and sand substrate.